2023
DOI: 10.1097/ta.0000000000003877
|View full text |Cite
|
Sign up to set email alerts
|

A novel miRNA mimic attenuates organ injury after hepatic ischemia/reperfusion

Abstract: INTRODUCTION: Extracellular cold-inducible RNA-binding protein (eCIRP) is a novel mediator of inflammation and tissue injury. It has been shown that miRNA 130b-3p acts as an endogenous inhibitor of eCIRP. Because RNA mimics are unstable after in vivo administration, we have chemically engineered miRNA 130b-3p mimic (named PS-OMe miR130) to improve its stability by protection from nuclease activity. We hypothesize that PS-OMe miR130 reduces eCIRP-mediated injury and inflammation in a murine model of hepatic isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Likewise, the differences in perfusion, drug delivery, and serum and tissue eCIRP concentrations after treatment may have important implications that have not been fully investigated in our study. Although we have not directly measured the specific changes to eCIRP in serum or tissues after treatment with PS-OME miR130, we have previously shown that eCIRP is increased in both serum and tissue after renal IR (20). In conjunction with our findings in the CIRPKO mice (35) and the results of our study showing a significant reduction in inflammation and injury, it can be reasoned that the initial strong binding affinity of the PS-OME miR130 with eCIRP would result in a decrease in eCIRP-mediated inflammatory signaling and thus indirectly reduce eCIRP levels in the treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Likewise, the differences in perfusion, drug delivery, and serum and tissue eCIRP concentrations after treatment may have important implications that have not been fully investigated in our study. Although we have not directly measured the specific changes to eCIRP in serum or tissues after treatment with PS-OME miR130, we have previously shown that eCIRP is increased in both serum and tissue after renal IR (20). In conjunction with our findings in the CIRPKO mice (35) and the results of our study showing a significant reduction in inflammation and injury, it can be reasoned that the initial strong binding affinity of the PS-OME miR130 with eCIRP would result in a decrease in eCIRP-mediated inflammatory signaling and thus indirectly reduce eCIRP levels in the treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that any miRNA is unstable in vivo because of its susceptibility to degradation by nucleases, miRNA 130b-3p was chemically engineered in an in effort to improve its stability and thereby increase its potential efficacy (41). Recently, this modified miRNA, which we termed PS-OME miR130, has shown to reduce inflammation and tissue injury in mice, which underwent either hepatic I/R or cecal ligation puncture sepsis (19,20). It has been shown that using surface plasmon resonance and three-dimensional computational modeling, PS-OME miR130 retained its binding affinity to eCIRP and that the binding was comparable to that which was observed with the unmodified miRNA 130b-3p (19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations